RATIO DECIDENDI HAKIM MENETAPKAN HAK HADHANAH ANAK DI BAWAH UMUR KEPADA BAPAKNYA PERSPEKTIF KOMPILASI HUKUM ISLAM (STUDI PUTUSAN NO. 2531/PDT.G/2021/PA.KAB.KDR.) (AL MUNAZHZHARAH, 2025)
Ratio Decidendi Judges Establish Hadhanah Rights of Minors to Their Fathers Perspective of Compilation of Islamic Law (Decision Study No. 2531/Pdt.G/PA/Kab.Kdr). Describe what is the ratio decidendi the judge determines the hadhanah rights of minors to their fathers in decision no. 2531/Pdt.G/2021/PA.Kab.Kdr, and what is the ratio decidendi of judges in deciding the hadhanah rights of minors to their fathers from the Perspective of Compilation of Islamic Law. The type of research used is qualitative research, in which the researcher is directly involved in the field or research location at the Religious Court of Kediri Regency, with the object of this research being judges at the Religious Court of Kediri Regency, who were interviewed regarding their opinion about the hadhanah case as a whole and their opinion about their decision regarding the case of Hadhanah Rights for minors fell to the father with Case Number 2531/Pdt.G/2021/PA.Kab.Kdr. The method used is the purposive sample method, with interview and documentation data collection techniques and then analyzed by combining and interpreting facts related to the judge's decision in the hadhanah case as a whole and the decision made by the judge in the hadhanah rights case for minors who fall to their father with Number Case 2531/Pdt.G/2021/PA.Kab.Kdr. The results of the research and discussion, the Ratio Decidendi used by judges in deciding hadhanah cases of minors based on the Child Protection Act No. 35 of 2014 Article 3: "child protection aims to ensure the fulfillment of children's rights so that they can live, grow, develop and participate optimally in accordance with human dignity and dignity, and receive protection from violence and discrimination, for the realization of quality Indonesian children, noble and prosperous", and the judge's ratio decidendi in deciding hadhanah cases from the perspective of the Compilation of Islamic Law, the judge refers to Article 105 (a) of the Compilation of Islamic Law when in general there is no dispute between the plaintiff and the defendant, the Compilation of Islamic Law is used, but if once the father knows that there is a problem with the mother or that the mother has made a mistake in the child's education, the judge rules out Article 105 (a) of the Compilation of Islamic Law.